Implementasi Pembelajaran Multibahasa dalam Meningkatkan Kemampuan Bahasa Asing Siswa di Sekolah Menengah - Fitania Idha Amarela; Nawang Hengki Saputra; Yevonnael Zebua (BADAN PENERBIT STIEPARI PRESS, 2022)
This study aims to analyze the implementation of multilingual education in enhancing students' foreign language skills in secondary schools. Multilingual education is an educational approach that involves the use of more than one language in the teaching and learning process, with the goal of comprehensively developing students' foreign language skills. The study employs a mixed-method approach, combining both qualitative and quantitative methods. The results indicate that multilingual education has a significant positive impact on improving students' foreign language abilities. Students engaged in multilingual learning show greater improvement in speaking, listening, reading, and writing skills in foreign languages compared to those in conventional learning settings. Factors such as a supportive learning environment, varied use of media, and more intensive interaction with the target language are key determinants of the success of this implementation.